2016
DOI: 10.1002/adfm.201604943
|View full text |Cite
|
Sign up to set email alerts
|

Activating Basal Planes and S‐Terminated Edges of MoS2 toward More Efficient Hydrogen Evolution

Abstract: Molybdenum disulfide (MoS2) has been considered as a promising alternative to platinum (Pt)‐based catalyst for hydrogen evolution reaction (HER) due to its low cost and high catalytic activity. However, stable 2H phase of MoS2 (2H‐MoS2) exhibits low catalytic activity in HER due to the inert basal plane and S‐edge. Thus, to exploit the basal plane and S‐edge for additional electrocatalytic activity, a facile strategy is developed to prepare P‐doped 2H‐MoS2 film on conductive substrate via low‐temperature heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 52 publications
1
94
0
Order By: Relevance
“…Also, the Δ G H* of Ni‐MoS 2 (–0.07 eV) was much lower than pristine MoS 2 (0.60 eV), which shows that the combination of intermediates H* into H 2 can occur spontaneously in thermodynamics. Similarly, Xue et al activated the S‐edge and basal plane of 2H‐MoS 2 by P doping . Due to the difficulty of P doping into the crystal structure of MoS 2 , oxygen codoping was utilized to dope P successfully into the basal plane of 2H‐MoS 2 .…”
Section: Electrocatalysts For Hermentioning
confidence: 99%
“…Also, the Δ G H* of Ni‐MoS 2 (–0.07 eV) was much lower than pristine MoS 2 (0.60 eV), which shows that the combination of intermediates H* into H 2 can occur spontaneously in thermodynamics. Similarly, Xue et al activated the S‐edge and basal plane of 2H‐MoS 2 by P doping . Due to the difficulty of P doping into the crystal structure of MoS 2 , oxygen codoping was utilized to dope P successfully into the basal plane of 2H‐MoS 2 .…”
Section: Electrocatalysts For Hermentioning
confidence: 99%
“…[27] P dopants might lead to phase separation, [28] and the stabilize the P dopants in MoS 2 needs oxygen co-doping. [29] Very recently, Li et al demonstrated that the intrinsic electrocatalytic activity of 2H-MoS 2 basal plane could be activated by introducing of S-vacancy and strain, providing a new strategy to activate the HER inert basal plane sites in MoS 2 catalysts. [30] Recently, MoSe 2 also has aroused much attention in HER catalysts due to its metallic nature compared with semiconducting MoS 2 .…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…N dopants can only activate the inert S‐edge rather than basal plane . P dopants might lead to phase separation, and the stabilize the P dopants in MoS 2 needs oxygen co‐doping . Very recently, Li et al demonstrated that the intrinsic electrocatalytic activity of 2H‐MoS 2 basal plane could be activated by introducing of S‐vacancy and strain, providing a new strategy to activate the HER inert basal plane sites in MoS 2 catalysts …”
Section: Introductionmentioning
confidence: 99%
“…[16] The binding energies of Mo 3d 3/2 and Mo 3d 5/2 are 235.6 and 232.4 eV, respectively, attributed to Mo 6þ in the form of MoO 4 2À . [17] Compared with the Mo 4þ in MoS 2 , [18] the doped Mo has a much higher binding energy, suggesting that Mo prefers to incorporate into the Ni 3 S 2 /Ni(OH) 2 composites with high oxidization states. In Figure 3d, the binding energy of 163.6 eV corresponds to the S 2À 2p 1/2 of Ni 3 S 2 .…”
Section: Resultsmentioning
confidence: 99%